A longer biodegradation process enhances the cadmium adsorption of the biochar derived from a manure mix. (June 2023) - Jiang, Yi; Xing, Yonghui; Liu, Song; Tan, Shuxin; Huang, Qiaoyun; Luo, Xuesong; Chen, Wenli
Abstract: Adsorption of heavy metals by biochar adsorbents can reduce their bioavailability and mobility. However, the effects of the biodegradation processes of raw material before biochar preparation on adsorption remain unclear. This study utilized the degradation products at different stages of the compost to produce biochars and investigated their adsorption property. Compared to the virgin biochar (IBC) prepared from untreated compost, the biochar (EBC and LBC) prepared from the sample collected by the biodegradation process had more robust adsorption properties. Furthermore, the adsorption capacity of biochar (LBC) prepared from the sample collected in the later biodegradation process was approximately 50% higher than that of biochar (EBC) prepared from the sample collected in the early phase. LBC had more oxygen-containing functional groups, more ion exchange sites, and carbonate ions, improving the adsorption capacity by 100% compared with IBC. The BET surface area of LBC was approximately four times higher than that of IBC and 25% more than EBC. Moreover, the dominant adsorption mechanism of LBC is the formation of insoluble Cd-mineral complexes (cadmium carbonate) with the inorganic. The increase in pH also facilitated Cd (II) precipitation. This study highlighted that appropriate biodegradation before biochar preparation from manure mix is an effective and energy-saving method to enhance the ability of biochar to adsorb heavy metals. Graphical abstract: Image 1 Highlights: A longer biodegradation process significantly increases surface area of biochar. The adsorption capacity of LBC is about 50% higher than that of EBC. The dominant mechanism of LBC is the formation of insoluble Cd-mineral complexes. A green method for efficient Cd (Ⅱ) remediation using waste biomass is provided.